Analytical subthreshold current and subthreshold swing models of short-channel dual-metal-gate (DMG) fully-depleted recessed-source/drain (Re-S/D) SOI MOSFETs - Saramekala G.K.; Santra A.; Kumar M.; Dubey S.; Jit S.; Tiwari P.K. (My University, 2025)
In this paper, analytical subthreshold current and subthreshold swing models are derived for the short-channel dual-metal-gate (DMG) fully-depleted (FD) recessed-source/ drain (Re-S/D) SOI MOSFETs considering that diffusion is the dominant current flow mechanism in subthreshold regime of the device operation. The two-dimensional (2D) channel potential is derived in terms of back surface potential and other device parameters. The so called virtual cathode potential in term of the minimum of back surface potential is also derived from 2D channel potential. The virtual cathode potential based subthreshold current and surface potential based subthreshold swing model results are extensively analyzed for various device parameters like the oxide and silicon thicknesses, thickness of source/drain extension in the BOX, control to screen gate length ratio and channel length. The numerical simulation results obtained from ATLASTM, a 2D numerical device simulator from SILVACO Inc have been used as a tool to verify the model results. © 2014 Springer Science+Business Media New York.